PERANCANGAN SISTEM INFORMASI RUMAH TRAVEL TOUR BAGI PERUSAHAN TOUR DAN TRAVEL - Desy Iba Ricoida (LPPM STMIK Pringsewu, 2017)
Technological developments require Tour and Travel companies to take advantage of technology to make maximazing of utilize technology quality of service to customers where customers now have the desire to get information and services quickly. Currently, many information systems have been developed by travel companies but are still only for one company, So that the development of information systems by adapting the concept of a marketplace that is devoted to a collection of travel tour company can be make a good company and customers can take advantage of this information system as a bridge of communication, information and transactions related to tour and travel. As for the design of this system is a case study is some tour and travel companies in the city of Palembang by using the RUP method, the selection of this method is due to the iterative software development process so it is possible to make improvements if the previous stage that allows to make improvements if the previous stage still needs improvement. The design of travel information systems travel tour using use case diagrams, activity diagrams, sequence diagrams, class diagrams and the design of interface system and will be implement by php and mySQL. , The result of this design is an information system which is a gathering place from some travel tour company, and can become a system of information linking process of transaction, information and communication between company and customer that allows to make improvements if the previous stage still needs improvement